The Teachers’ Utilization of the Most Essential Learning Competencies (MELCS) and its Relation to the Learning Development of Grade Six Pupils in a Public School in the Philippines: Basis for a Proposed Program - Zalun, Judy G. (Future Science / FSH-PH Publications, 2023)
In education, ensuring that students develop the necessary knowledge and skills is critical, especially when faced with challenges in learning delivery. The Department of Education (DepEd) in the Philippines has implemented the Most Essential Learning Competencies (MELCs) to guide the curriculum and instruction in all public schools. MELCs were developed in response to the changing educational landscape brought on by the COVID-19 pandemic. MELCs aim to ensure that students gain the necessary competencies and skills for future success. The goal of MELCs is to ensure that students acquire the necessary competencies and skills that are essential for their future success. MELCs assist educators in designing and delivering effective learning experiences that align with the needs and goals of the curriculum. This study investigated the impact of utilizing Most Essential Learning Competencies (MELCs) on the academic development of Grade Six students in public schools in the Philippines during the academic year 2021-2022. Data was collected from 173 teachers and 67 master teachers using a descriptive research design. Results showed that MELCs were highly utilized in aligning lessons to content-area standards, providing flexible activities, congruent lesson planning, delivering assessment questions, and planning a learning process. Grade Six students showed outstanding cognitive, affective, and psychomotor development through the use of MELCs. However, teachers faced challenges such as lack of cooperation from parents and students, lack of financial resources, and lack of learning resources. Recommendations include seeking parental cooperation, providing additional learning resources, establishing a monitoring system, and offering interventions for students.